2010
DOI: 10.3238/arztebl.2010.0622
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Tonsillitis in Adults

Abstract: Although this study had a number of limitations (small size, retrospective design, short follow-up), it was able to show that tonsillectomy for adults with recurrent tonsillitis improves health and quality of life and reduces the need to consume medical resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…This could be due to difference in age and sex distribution of the studies. Oluwasanmi et al reported the overall improvement in quality of life after tonsillectomy compared to before surgery that is same line with the findings of our study (24).…”
Section: Advances In Bioscience and Clinical Medicinesupporting
confidence: 93%
“…This could be due to difference in age and sex distribution of the studies. Oluwasanmi et al reported the overall improvement in quality of life after tonsillectomy compared to before surgery that is same line with the findings of our study (24).…”
Section: Advances In Bioscience and Clinical Medicinesupporting
confidence: 93%
“…Stafford, for instance, concluded that the effect of TE is not superior to conservative treatment but he followed only 40 patients in total [85]. In contrast to this statement a more recent study concluded, that the quality of life significantly improved after TE [86]. Comparable studies are currently undertaken in the UK as an answer to the restrictions of the National Health System (NHS) [87].…”
Section: Discussionmentioning
confidence: 99%
“…В Германии, ежегодно проводится около 115 000 ТЭ. Показанием к операции является хронический или рецидивирующий тонзиллит [10].…”
Section: «научный диалог: вопросы медицины»unclassified